A new in vitro test to evaluate the resistance level against acaricides of the cattle tick, Rhipicephalus (Boophilus) microplus - Lovis, Leonore (My University, 2011)
In this article we present a new bioassay to assess the resistance status of ticks to acaricides. The larval tarsal test (LTT) is a sensitive, highly time-effective in vitro test. It allows the investigation of a large number of compounds and doses on the cattle tick Rhipicephalus (Boophilus) microplus in a short period of time. The ability of the LTT to assess the lethal concentration at 50% mortality (LC50) and resistance ratios (RRs) of a susceptible and a resistant R. microplus strain was compared with the FAO-recommended Larval Packet Test (LPT). Representative compounds of the carbamate, organophosphate (OP), synthetic pyrethroid (SP), formamidine (FOR), macrocyclic lactone and pyrazole classes were used for this comparison. The resistance status against OP, SP and FOR of the resistant R. microplus strain was confirmed in vivo. The LTT resulted in resistance ratios comparable to those obtained with the LPT. However, the lethal concentrations were up to 150-fold lower in the LTT than the in LPT. The advantage of the LTT is to simplify the methodology by avoiding the handling of larvae and using multi-well plates. The LTT is therefore a suitable test for the assessment of the level of resistance of R. microplus and is very promising to evaluate the resistance profile of field strains. Additionally, the LTT is also suitable to test other ixodid species.
Keywords: Rhipicephalus (Boophilus) microplus; Resistance; Larval test; Bioassay; Acaricide